The Cognitive and Affective Changes Caused by the Differentiated Classroom Environment Designed for the Subject of Poetry - (:unkn) unknown (EDAM, 2009)
The purpose of this research is to analyze the cognitive ( learning level) and affective (volunteering to study together, attitude towards the teacher and the lesson) changes which are caused by the differential classroom environment designed for the poetry subject in a Turkish lesson of the 6th grade in elementary education. Theory testing technique of case study which takes place in qualitative research was applied in this research. This research was implemented on 22 students who attended sixth grade in a private school in Istanbul. Differentiated teaching design, which was prepared by using station and interest center strategies, was exercised in the subject of poetry in a Turkish lesson for two teaching periods. Data which were obtained via in a depth individual interview with the teacher, focus group interviews with five students, and direct observations were analyzed with structured reporting method. According to the findings, differentiated teaching has a positive impact on children's learning. In addition, it increases the interests of children towards the lesson, help them develop friendship relationships, and augments mutual aid behaviors.
Keywords: Differentiated Instruction; Station Strategy; Interest Centers Strategy; Teaching Turkish Language; INSTRUCTION; STANDARDS